The impact of panda diplomacy on the relationship of trade and perception of China - Sun, Xi (2020)
China has increased Although China has send panda as gift to foreign countries since Tang dynasty, this practice is not known and recognized as a public diplomacy until recent decades. The universal appeal of panda make this public diplomacy so successful in getting favourable public opinion in selected foreign countries and building a long-time cooperation with their international partners in its attempt to shape its global image. Now, panda has become the unique diplomatic tool and important symbol to China.